Pengaruh Kepribadian Agreeableness dan Conscientiousness terhadap Academic Dishonest: Studi Empiris Mahasiswa Akuntansi Perguruan Tinggi di Kota Padang - Aldian Fahdri; Herlina Helmy (Jurnal Eksplorasi Akuntansi, 2023)
Academic dishonesty is still common among academics and is mostly done by students today and this is major concern. Accounting research needs to pay attention to this phenomenon. This study aims to analyze the effect of agreeableness and conscientiousness on academic dishonesty. This type of research is associative causality research with a quantitative approach. The population in this study were undergraduate students of Accounting, Faculty of Economics, Padang State University, Andalas University, Bung Hatta University and the Computer College Foundation, Putra Indonesia University. The number of research samples was determined using the slovin formula. The samples in this study were undergraduate Accounting students who were active at Padang State University, Andalas University, Bung Hatta University, and the University Putra Indonesia Computer College Foundation. The data collection method used a questionnaire distributed in the form of a google form. The data used in this study is primary data. The hypothesis in this study was tested using multiple linear regression analysis with IBM SPSS 25. The results showed that agreeableness and conscientiousness had a significant and negative effect on academic dishonesty.